Infection to hypertension: a review of post-COVID-19 new-onset hypertension prevalence and potential underlying mechanisms - Teymourzadeh, Azin; Abramov, Dmitry; Norouzi, Sayna; Grewal, Dennis; Heidari-Bateni, Giv (Frontiers in Cardiovascular Medicine, 2025)
Post-COVID new-onset hypertension (PCNH) is an increasingly reported complication among COVID-19 survivors. PCNH can emerge up to 12 months postinfection, with elevated risks observed among older patients, particularly those who experienced severe COVID-19, and among females, implicating the possibility of age and hormonal influence. Leading theories converge on enduring dysregulation of the angiotensin pathway and endothelial dysfunction. In addition to renin–angiotensin alterations, sustained inflammation, lung vascular damage, deconditioning, and mental health decline may also impact the likelihood of PCNH. Conventional renin–angiotensin system (RAS) antagonists may help improve pathway distortions, while novel anti-inflammatory agents and recombinant ACE2 biologics can help mitigate endothelial injury to alleviate cardiovascular burden. This review highlights the multifaceted mechanisms driving PCNH and the need to elucidate timing, predictors, pathophysiology, and tailored interventions to address this parallel pandemic among COVID-19 survivors.